1977
DOI: 10.2307/3897461
|View full text |Cite
|
Sign up to set email alerts
|

Root Phenology as a Factor of Competition among Grass Seedlings

Abstract: Highlight: Roots of plants express phenology significant to readily invade and become established on disturbed sites. competitive relationships, as do aerial parts. The following devel-Favorable root phenology is one of the adaptive strategies opmental stages of root phenology are proposed: (1) germination, allowing this superior competitive ability. (Perhaps the same (2) initial root growth, (3) rapid extension of root-soil contact, (4) dormancy, and (5) death. Examples of root phenological develop-principles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 2 publications
1
68
0
Order By: Relevance
“…Pathways by which B. tectorum facilitate its expansion are myriad and include phenotypic plasticity to new host environments [2], it increases the rates and sizes of wildfires, which fosters more invasion [3], rapid above-and below-ground growth rates [4,5], prolific seed production [6], landscape disturbance [7][8][9], and elevated atmospheric CO 2 [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Pathways by which B. tectorum facilitate its expansion are myriad and include phenotypic plasticity to new host environments [2], it increases the rates and sizes of wildfires, which fosters more invasion [3], rapid above-and below-ground growth rates [4,5], prolific seed production [6], landscape disturbance [7][8][9], and elevated atmospheric CO 2 [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers reported rooting depths of over 39 inches in root box studies (Harris 1967) and over 59 inches deep under field conditions (Hironaka 1961;Hulbert 1955). Harris (1977) indicated that downy brome roots grow 7 to 8 inches deep before lateral roots develop and lateral roots then tend to grow more downward than horizontally. Lateral root growth was reported to be 8 to 12 inches (Hulbert 1955).…”
Section: Downy Brome Seedling Establishmentmentioning
confidence: 95%
“…Downy brome roots will continue to grow in very dry soils. Downy brome roots have poorly developed endodermis and suberized casparian strips to insulate against hot, dry soil and drought (Harris 1977). High air temperatures cause leaf water potentials to drop and roots cannot absorb soil moisture fast enough to keep plants from desiccating.…”
Section: Downy Brome Seedling Establishmentmentioning
confidence: 99%
See 1 more Smart Citation
“…By 2005, 107 parcels totaling 295,700 acres had been incorporated into the Stewardship Trust. 7 The purpose of Colorado Stewardship Trust lands is to protect long-term productivity and sound stewardship instead of maximizing returns to the trusts. These lands are not guaranteed to remain as open space forever because an 80% majority vote of the Land Board commissioners can remove them from the Stewardship Trust rolls.…”
Section: Sidebar 3 the Bureau Of Land Management And The Empire Rancmentioning
confidence: 99%